Relationship of lipoprotein-associated apolipoprotein C-III to lipid variables and coronary artery disease risk: The EPIC-Norfolk Prospective Population Study - van Capelleveen, Julian C. (J Clin Lipidol, 2018)
BACKGROUND: Plasma apolipoprotein C-III (apoC-III) levels are associated with coronary artery disease (CAD) risk. OBJECTIVE: To assess whether lipoprotein-associated apoC-III levels predict risk of CAD events. METHODS: ApoC-III associated with apoB, apoAI, and Lp(a) (apoCIII-apoB, apoCIII-apoAI and apoCIII-Lp(a), respectively) were measured using high-throughput chemiluminescent enzyme-linked immunoassays (ELISA) in 2711 subjects (1879 controls and 832 cases with CAD) in the EPIC-Norfolk prospective population study with 7.4 years of follow-up. These measures were correlated with a variety of lipid measurements and the presence of CAD. The indices of “total apoCIII-apoB” and ‘total apoCIII-apoAI” were derived by multiplying plasma apoB and apoAI, respectively. RESULTS: ApoCIII-apoB (p=0.001), apoCIII-Lp(a) (p<0.001), apoCIII-apoAI (p=0.005) were higher in cases vs controls, tended to correlate positively with BMI, hsCRP, apoCIII, LDL-C, triglycerides, remnant cholesterol, VLDL, LDL and HDL particle number and VLDL size, but negatively with LDL and HDL particle size (p<0.001 for all). ApoCIII-ApoB, apoCIII-apoAI, apoCIII-Lp(a), total apoCIII-Lp(a) and total apoCIII-apoB were predictors of CAD after adjustment of age, sex, BMI, smoking, diabetes, hypertensive and lipid lowering drug use, but they lost their significance following further adjustment of lipid and lipoprotein variables. In contrast, apoCIII remained a significant risk predictor with multivariable adjustment. CONCLUSIONS: This study suggests that ELISA-measured lipoprotein-associated apoCIII markers reflect atherogenic lipid particles but, as opposed to total plasma apoCIII, do not independently predict risk of CAD events.